2007
DOI: 10.1111/j.1447-0756.2007.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitor‐induced bone mineral loss and its prevention by bisphosphonate administration in postmenopausal breast cancer patients

Abstract: AI carries a potential risk of bone mineral loss despite the short therapy duration. Bisphosphonate has a preventive effect on this loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In our study, BMD loss was observed in 62.0% of patients in the ANA alone group, while only 26.9% of patients had a BMD loss in the combination bisphosphonate group. The findings of AIinduced BMD loss and its prevention by bisphosphonates agree with previous reports [6,[15][16][17][18][19][20]. In postmenopausal women, there is an established concept that circulating estrogens, most of which are minimal and unmeasurable by conventional RIA methods, are derived from aromatization in peripheral adipose tissue [21].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, BMD loss was observed in 62.0% of patients in the ANA alone group, while only 26.9% of patients had a BMD loss in the combination bisphosphonate group. The findings of AIinduced BMD loss and its prevention by bisphosphonates agree with previous reports [6,[15][16][17][18][19][20]. In postmenopausal women, there is an established concept that circulating estrogens, most of which are minimal and unmeasurable by conventional RIA methods, are derived from aromatization in peripheral adipose tissue [21].…”
Section: Discussionsupporting
confidence: 90%
“…An assessment of fracture risk based upon clinical risk factors, coupled with dual‐energy X‐ray absorptiometry (DXA) of the hip and lumbar spine is reasonable in older patients (>60 years) initiating AIs . Bisphosphonate therapy or denosumab could be considered in those assessed as being at high baseline fracture risk (e.g. women with established osteoporosis or FRAX‐determined 10‐year probability of major osteoporotic fracture >20%.…”
Section: Hormonal Treatmentsmentioning
confidence: 99%
“…In a study by Yonehara et al . [44], there was a significant increase in BMD in a group of women treated with bisphosphonate. The study, however, included only 17 patients.…”
Section: Treatment and Prophylactics Of The Aromatase Inhibitor‐inducmentioning
confidence: 99%